The Effect of Lone Motherhood on the Smoking Behaviour of Young Adults - Marco Francesconi; Stephen P. Jenkins; Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We provide evidence that living with an unmarried mother during childhood raises smoking propensities for young adults in Germany.
Keywords: I10; J12; J18; 330; smoking; lone parent; childhood family structure; divorce; unobserved heterogeneity